2013
DOI: 10.1073/pnas.1305175110
|View full text |Cite
|
Sign up to set email alerts
|

Integration of epigenetic and genetic controls of seed size by cytokinin in Arabidopsis

Abstract: The development of seeds in flowering plants is placed under complex interactions between maternal tissues, the embryo, and the endosperm. The endosperm plays a major role in the regulation of seed size. In Arabidopsis thaliana, endosperm size depends on the coordination of the genetic pathway HAIKU (IKU) with epigenetic controls comprising genome dosage, DNA methylation, and trimethylated lysine 27 on histone H3 (H3K27me3) deposition. However, the effectors that integrate these pathways have remained unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 62 publications
(63 reference statements)
3
93
0
Order By: Relevance
“…In the LCM dataset, however, all four genes were called present and at least weakly expressed within the suspensor. We also compared the different suspensor data sets for presence of previously described endosperm-specific genes (Kinoshita et al, 1999(Kinoshita et al, , 2004Luo et al, 2000;Kang et al, 2008;Li et al, 2013;Barthole et al, 2014). The LCM results show all six genes tested as present, whereas our data indicate that only two out of six are also at least weakly expressed in the suspensor (supplementary material Table S10) and those two were also detected in a RNA-seq transcriptome analysis (Nodine and Bartel, 2012).…”
Section: Nuclear Transcriptomic Data As Proxy For Gene Expression Promentioning
confidence: 81%
“…In the LCM dataset, however, all four genes were called present and at least weakly expressed within the suspensor. We also compared the different suspensor data sets for presence of previously described endosperm-specific genes (Kinoshita et al, 1999(Kinoshita et al, , 2004Luo et al, 2000;Kang et al, 2008;Li et al, 2013;Barthole et al, 2014). The LCM results show all six genes tested as present, whereas our data indicate that only two out of six are also at least weakly expressed in the suspensor (supplementary material Table S10) and those two were also detected in a RNA-seq transcriptome analysis (Nodine and Bartel, 2012).…”
Section: Nuclear Transcriptomic Data As Proxy For Gene Expression Promentioning
confidence: 81%
“…Seed formation requires extensive intergenerational and intertissue communication and coordination (Garcia et al, 2005;Ingouff et al, 2006;Ingram, 2010;Li et al, 2013;Xu et al, 2016). Angiosperm seeds consist of three genetically distinct entities: the diploid embryo, with one paternal and one maternal genome; the triploid endosperm, with two maternal and one paternal genome; and the protective integuments/seed coat, consisting of diploid maternal tissue from the previous generation (Fig.…”
Section: A Brief Primer On Endosperm Development and Functionmentioning
confidence: 99%
“…Perturbation of the machinery that contributes to gene expression in the endosperm can lead to alterations in seed size (Xiao et al 2006;Kradolfer et al 2013;Li et al 2013). To quantify the effect of PKL and/or PKR2 on seed size, we scored the mean seed areas of WT, pkl, pkr2, and pkl pkr2 seeds as described previously (Herridge et al 2011).…”
Section: Pkl and Pkr2 Antagonistically Influence Seed Sizementioning
confidence: 99%
“…However, we found no evidence of differences in embryo development or seed set in pkl pkr2 plants relative to pkl plants ( Figure S5 and Table S6). Thus, rather than observing phenotypic enhancement by the loss of both paralogs, our data indicated that these traits are not PKR2 dependent.Perturbation of the machinery that contributes to gene expression in the endosperm can lead to alterations in seed size (Xiao et al 2006;Kradolfer et al 2013;Li et al 2013). To quantify the effect of PKL and/or PKR2 on seed size, we scored the mean seed areas of WT, pkl, pkr2, and pkl pkr2 seeds as described previously (Herridge et al 2011).…”
mentioning
confidence: 99%